Lectoescritura (dislexia y disortografia) y su incidencia en el aprendizaje de los estudiantes del octavo año de educación básica de la unidad educativa Nicolás Infante Díaz del cantón Quevedo - Ruiz Morales, Antonia Marianela (2016)
The reading-writing comes related to the reading and writing is a disorder, when the students not have practice in the dictated. Writing dyslexia therefore the Disortografía writes as pronounce bone confuses the lyrics. Teachers must help students to see that such knowledge are the students and if you know to identify words. There are many students who have difficulties, write in write the way you talk. There are varied methods and theories about how lead to good port the process of literacy, for example, some is focused in aspects more shape you then treat the process from its parts toward the general, i.e. on the basis of the, next letter by syllables, then move through the words and finally by the sentences; and on the other hand, the so-called constructivist, proposed that the perception of the child starts being a mixture, capturing the entire, without stopping in the details, then depart at all and have the child complete words with their relevant meanings. The problems of the learning is da by different factors as: method pedagogical inappropriate, the structure family, he environment social, adaptation maturity for the learning, deficiency sensory, problems emotional and behavioural, on protection or abandonment emotional, conflicts family.